Structural and electric properties of Ce‐doped Na0.5Bi4.5Ti4O15 piezoceramics with high Curie temperatures. Issue 8 (13th March 2020) - Qin, Lu; Jiang, Chaobin; Liu, Kanghui; Chen, Ye; Du, Yike; Zuo, Yuandong; Chen, Yong; Cao, Wanqiang
Abstract: Na0.5 Bi4.5‐ x Ce x Ti4 O15 ( x = 0, 0.02, 0.04, 0.06, 0.08, 0.10) lead‐free piezoelectric ceramics with high Curie temperatures are fabricated using the conventional solid‐phase method. The effects of the Ce content on the phase structures, morphologies, and electrical properties of the Na0.5 Bi4.5‐ x Ce x Ti4 O15 ceramics are systematically investigated. The appropriate content of Ce increases b/a and c/a and induces the distortion of the crystal structure. The increased b/a leads to a transverse asymmetry of the Na0.5 Bi4.5‐ x Ce x Ti4 O15 ceramics, which facilitates the dipole flipping, thus enhancing the piezoelectric properties ( d 33 = 20 pC/N). Although the improved c/a increases the degree of tetragonality of the Na0.5 Bi4.5‐ x Ce x Ti4 O15 ceramic, which decreases the Curie temperature ( T C ), the T C values of all samples are higher than 600°C, considerably higher than the practical application temperature. The Ce doping significantly reduces the dielectric loss of the sample and increases its dielectric performance. The improvements in electric properties by the cerium doping can expand its use in high‐temperature environments for oilfield logging, aerospace, and military applications.